Canine mitral valve disease: investigating the role of miR-143 in valvular interstitial cell activation - Finch, Ellen (Tufts University Tisch Library, 2025)
This report documents a summer research project conducted in the Yang Lab, focusing on investigating miR-143's role in the activation of canine valvular interstitial cells (VICs) associated with myxomatous mitral valve disease (MMVD). The findings aim to increase our understanding of the molecular mechanisms underlying this condition, potentially informing future therapeutic strategies.; Mentor: Vicky Yang; Cummings School of Veterinary Medicine Student Summer Research 2025.